HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN TINGKAT KECEMASAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Fajri ' Alfiannur; Fathra Annis Nauli; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   Spiritual intelligence is relatively with mental tranquillity, so it will have affect the anxiety of patients undergoing hemodialysis. The aim of this research was to identify the correlation between spiritual intelligence with the anxiety levels of hemodialysis patients in  hemodialysis room of Arifin Achmad Hospital Pekanbaru. The design was descriptive correlation research with cross sectional approach. The sampling technique sample purposive sampling involving 30 respondents that was selected based on inclusion and exlusion criteria. This research used questionnaire for spiritual intelligence and questionnaire Zung Anxiety Self-Assessment Scale for anxiety. The analysis used univariate analysis to determine the frequency distribution and bivariate using Kolmogorof Smirnov. The results showed that  respondents who had high spiritual intelligence, 36,7% experienced mild to moderate anxiety, while respondents who had spiritual intelligence moderate, 20% experienced a panic. The results of the statistical test Kolmogorof Smirnov was obtained p value  (0,036) <α (0.05), which means that there is a correlation between spiritual intelligence with the level of anxiety in hemodialysis patients  . Results of this study are advised to be used by hospitals to improve the quality of services and procedures using a holistic approach, to observe of patients from biological, psychological, social and spiritual persepective for hemodalysis patient so that hemodalysis patient anxiety can be reduced. Keywords: Anxiety, chronic renal failure, hemodialysis, spiritual intelligence   References: 24 (2003-2014)